Surrealism and Abbas Abdullah in Kurdish Poetry - Hawez, srusht J.; Abdullah, Ahmed M. (Mitanni Journal of Humanitarian Sciences, 2022)
The serialism method in the last century brought back the need for reality after the Dadaism method. It had a significant reflection on world literature and Kurdish literature. It has had an effect on embodying the feelings of writers, intellectuals, and artists, especially in the unpleasant reality in which they lived for the purpose of raising awareness of the groups of society. In this method, the poets imaging their internal feeling and reflect it in a high performance, Here the phenomenon of the obvious characteristics of serialism in poetry Abbas Abdullah’s poems, for example who is one of the modern Kurdish poets, open the field in front of our investigation directly. Serialism in Abbas Abdullah’s poems is an attempt to read the characteristics of Surrealism and Abbas’s poems also according to serialism method. The area of this research is special to the concept of serialism in poetry, particularly Abbas Abdullah’s poems. Our investigation is in this context so that we can clarify the details of all aspects of this literary approach and Abbas’s poetry in this regard. All historical, critical, and practical methods have been used in this research, and the research conducted two main chapters with an introduction and results in conclusion. The references and summary of the research in three different languages can be seen at the end of the research. In the first chapter, the concept and history of serialism and the characteristics, principles of serialism were discussed. In the second chapter, the reflection of serialism in Abbas’s poems has been described such as (Dreaming, unconscious feeling, automatic writing, incredible, irony, madness).